Prevalensi Sindroma Metabolik Non DM di RSUD Koja, Jakarta Periode Tahun 2000-2004 - Mardi Santoso; Susanna Ndraha; Jeffry Jeffry; Hartono Gunarso (Jurnal Kedokteran Meditek, 2004)
This research was aimed to know the prevalence of non diabetic metabolic syndrome toits related topics. Data hs collected from 384 hospitalized patients with Non diabetic Metabolic Syndrome 100 person’s sample are choosed with simple random sampling. This research is done by cross sectional method In RSUD Koja period 1st January 2000-18th November 2004. From this research, it is found that the prevalence of non diabetic metabolic syndrome in males were 56,4 %. Age between 51-89 years old , 69,3%. Age between 41-50 years old, 17,9%. Age between 31-40 years old, 7,7%. Age between 91-100 years old, 5,1%, family with economic and social problem (GAKIN), 64,1%. Family with non economic and social problem (Non GAKIN), 35,9%. Triglyceride level <150 mg/dl, the prevalence is 76,9%. Triglyceride level > 150 mg/ dl, 23,1%. HDL level <40mg/dl the prevalences is 69,2% . HDL level >40 mg/dl the prevalences is 30,8%. Systolic pressure ,140 mmHg, the prevalence is 35,9%. Systolic pressure > 140 mmHg, 64,1%. Diastolic pressure <90 mmHg, the prevalence is 30,8%. Diastolic pressure > 90 mmHg, 69,2%. After accomplishing this research, We summarize the prevalence of non diabetic metabolic syndrome in related with unmanageable factors (age, sex and family income) and with the manageable factors (Trygliceride level, HDL level, systolic pressure, diastolic pressure) at RSUD koja.